2016
DOI: 10.1016/j.lfs.2016.02.091
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of aerobic exercise and l -arginine ingestion on blood pressure in normotensive postmenopausal women: A crossover study

Abstract: After menopause the incidence of cardiovascular diseases increases in women. A decrease in nitric oxide (NO) bioavailability has been pointed out to play a major role in this phenomenon. Since it is believed that l-arginine administration could improve NO bioavailability, the aim of this study was to examine the effects of acute l-arginine administration associated with aerobic exercise on blood pressure (BP), redox state and inflammatory biomarkers in normotensive postmenopausal women (NPW). Sixteen volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 41 publications
3
39
0
9
Order By: Relevance
“…The initial search identified a total of seven hundred and ninety-two (792) studies. After reading the titles and abstracts, twenty-seven (27) were found to be duplicates, seven hundred and six (706) did not answer the research question and one study (01) was not available in full. Thus, twenty-three (23) studies constituted the final sample of this review (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial search identified a total of seven hundred and ninety-two (792) studies. After reading the titles and abstracts, twenty-seven (27) were found to be duplicates, seven hundred and six (706) did not answer the research question and one study (01) was not available in full. Thus, twenty-three (23) studies constituted the final sample of this review (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…This category consisted of eight studies [25][26][27][28][29][30][31][32] with results related to the cardiovascular benefits if regular exercise in menopausal women. Three studies [25][26][27] demonstrated that exercise in postmenopausal women results in the elevation of antioxidant system, measured by the enzymes superoxide dismutase and glutathione peroxidase. These enzymes are primordial in the oxidative stress process and necessary for the maintenance of life, since they prevent and control the excessive production of free radicals involved in the reactions that trigger the incidence of oxidative damage 26 .…”
Section: Physical Exercise As a Strategy For The Prevention Of Cardiomentioning
confidence: 99%
See 1 more Smart Citation
“…Is there an endothelial dysfunction after menopause? Previous studies have systematically shown that NO/cGMP signaling pathway, as well as flow-mediated dilation, is not impaired in hypertensive postmenopausal women as compared with normotensive subjects (Sponton et al, 2014;Puga et al, 2016;Jarrete et al, 2016;Novais et al, 2017). Additionally, both hypertensive and normotensive postmenopausal women were responsive to aerobic exercise training (AET) by increasing the endothelial biomarkers related to NO/cGMP pathway (Sponton et al, 2010;Rezende et al, 2011).…”
mentioning
confidence: 99%
“…SCOTT et al, 2015;PUGA et al, 2016;MEDEIROS-LIMA et al, 2017). No presente estudo, a caminhada máxima não modificou o NO sanguíneo e aumentou a expressão da eNOS no músculo afetado pela doença.…”
unclassified